Information and Communication Technologies for Ageing Well and e-Health c - Bamidis, Panagiotis D.; Ziefle, Martina; Maciaszek, Leszek A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book constitutes the thoroughly refereed proceedings of the third International Conference on Communication Technologies for Ageing Well and e-Health, ICT4AWE 2018, held in Funchal, Madeira, Portugal in March 2018. The 10 full papers presented were carefully reviewed and selected from 32 submissions. The papers aim at contributing to the understanding of relevant trends of current research on ICT for Ageing Well and eHealth including the ambient assisted living.
Keywords: Health informatics; User interfaces (Computer systems).; Health Informatics; User Interfaces and Human Computer Interaction